Disease spread, susceptibility and infection intensity: vicious circles? - Beldomenico, Pablo Martín (2010)
Epidemiological models and studies of disease ecology typically ignore the role of host condition and immunocompetence when trying to explain the distribution and dynamics of infections and their impact on host dynamics. Recent research, however, indicates that host susceptibility should be considered carefully if we are to understand the mechanism by which parasite dynamics influence host dynamics and vice versa. Studies in insects, fish, amphibians and rodents show that infection occurrence and intensity are more probable and more severe in individuals with an underlying poor condition. Moreover, infection itself results in further deterioration of the host and a 'vicious circle' is created. We argue that this potential synergy between host susceptibility and infection should be more widely acknowledged in disease ecology research.